Menyongsong Lahirnya Kompetensi Multikultural - Anwar, Ahmad Khoirul; Toekio, Soegeng (KEMADHA, 2011)
World Arts  is an  inherent part of human  life and  the  land  to work out any sense would think in the form of objects. Visual arts emerged as an important part  in  the  scope of material culture and continue  to grow  in  line with  the dynamics  people. Therefore much  art  work  produced  by  artists which capable of pouring creativity through various media and occurred in various areas,including  in  Indonesia.When  we  try  to  listen  to  cultural  wealth  of nations, both verbal and non verbal, either primary or secular , would look so rich source garapnya. In these cultural treasures, the source of work posted very pour , very diverse, even comes with a power generating common outside. There are charm and unique taste it bears, including the diversity of form is loaded with symbolism and value adhi. From several sources mentioned that the aspect of literacy work of art  it  is possible  to maturation media-character or moral reason which was rejected on the mores (ie, on the basis of norms of behavior habits, customs).Since  the socio-political atmosphere culminated  into a situation  that brings an update on various aspects of life, the existence of art seem slightly delayed echo nya.Dua  three decades before  the millennium,  the existence of  the art of singing was enough to inspire a lot of the hype. State-laden islands local culture, was rushed to reinvent its image in the middle of a worldwide cultural upheaval. This does not mean that whats been growing and developing is a deviation from the existing cultural roots. Many observers have even glanced at the art of cultural behaviors that tend to compromise on the aspirations of the people who heterogin and dynamics of  the  times.Similarly,  brief  exposure  can  I  convey  on  this  occasion,  and  as  a reflection of all that appears also in the works of artists on display and deliver meaningful messages for you in coverage mengapresiasikannya as the impact the  results of  the artist  / artists.